Paper : paging through history - Kurlansky, Mark (W.W. Norton & Company, 2016)
Paper is one of the simplest and most essential pieces of human technology. For the past two millennia, the ability to produce it in ever more efficient ways has supported the proliferation of literacy, media, religion, education, commerce, and art. It has created civilizations, fostering the fomenting of revolutions and the stabilizing of regimes. Witness history's greatest press run, which produced 6.5 billion copies of Mao zhu xi yu lu, Quotations from Chairman Mao Tse-tung (Zedong), or the fact that Leonardo da Vinci left behind only 15 paintings but 4,000 works on paper. Now, on the cusp of "going paperless"--And amid rampant speculation about the effects of a digitally dependent society-we've come to a world-historic juncture to examine what paper means to civilization. Through tracing paper's evolution, Mark Kurlansky challenges common assumptions about technology's influence, affirming that paper is here to stay. 'Paper' will be the history that guides us forward in the twenty-first century and illuminates our times.